NOVEL PRERETINAL HAIR PIN–LIKE VESSEL IN RETINAL ASTROCYTIC HAMARTOMA WITH VITREOUS HEMORRHAGE. Issue Volume 12:Issues 3(2018) (2018) - Soeta, Megumi; Arai, Yusuke; Takahashi, Hidenori; Fujino, Yujiro; Tanabe, Tatsuro; Inoue, Yuji; Kawashima, Hidetoshi
Abstract : Backgroud/Purpose: To report a case of retinal astrocytic hamartoma with vitreous hemorrhage and a hair pin-like vessel adhering to a posterior vitreous membrane. A 33-year-old man with a retinal astrocytic hamartoma presented with vitreous hemorrhage 5 times. Methods: Multimodal imaging, including fundus photography, fluorescein angiography, optical coherence tomography, and B-mode ultrasonography. Results: Multimodal imaging demonstrated a novel hair pin-like vessel that adhered to the posterior vitreous membrane. Conclusion: Some cases of retinal astrocytic hamartoma with vitreous hemorrhage may be related to structure abnormalities of tumor vessels. Abstract : Vitreous hemorrhage with a novel hair pin-like vessel occurred in the setting of retinal astrocytic hamartoma. Using multimodal imaging, a hair pin-like vessel adhering to the posterior vitreous membrane from a retinal astrocytic hamartoma was observed.